Team Monitoring, Does it Matter for Team Performance? Moderating role of Team Monitoring on Team Psychological Safety and Team Learning - Tarman Budianto; Ely Susanto; Sari Sitalaksmi; Gugup Kismono (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction: The use of work teams is a strategy that allows organizations to move faster and more proactively. Team performance is an interesting issue that needs to be studied more extensively. Background Problems: Team psychological safety and team learning have a positive effect on team performance. But in some of the literature, psychological safety has also been shown to have a negative impact on teams when team monitoring is low. This research was conducted to investigate the moderation role of team monitoring and the influence of team learning and team psychological safety on team performance. Novelty: This research contributes new insights related with team monitoring and its interaction to team learning and team psychological safety on team performance. Team psychological safety has been proven to be able to directly influence team performance indirectly through team learning, but we tested the two separately. Research Methods: This study involved 215 respondents who joined 38 teams. The collected data were analyzed using a regression analysis and bootstrap techniques. Findings: Team monitoring has been shown to have a moderate role in influencing team learning on team performance, but it has not been proven to influence team psychological safety on team performance. The learning and psychological safety of each team proved to have a direct effect on team performance. Conclusion: This paper can guide managers since, at a certain level team monitoring can improve team performance, but too much team monitoring actually has no effect on team performance. Managers need to consider team monitoring policies carefully, to optimizing team performance by managing team learning and building team psychological safety.